Low frequency signal spectrum analysis for strong earthquakes - Rozhnoi, Alexander; Solovieva, Maria; Biagi, Pier Francesco; Schwingenschuh, Konrad; Hayakawa, Masashi (Annals of Geophysics, 2012)
We examined changes in the spectral composition of the low frequency (LF) subionospheric signals from the NRK transmitter (37.5 kHz) in Iceland that were received in Bari (Italy) relative to the earthquake that occurred in L’Aquila on April 6, 2009. In our previous studies, we have reported the occurrence of preseismic night-time anomalies using observations from three receivers located in Bari, Graz (Austria) and Moscow (Russia). The strongest anomalies in the signals were observed in the NRK-Bari propagation path during the period 5-6 days before the L’Aquila earthquake, as well as during the series of aftershocks. During this period, similar very low frequency (VLF)/LF amplitude anomalies were also observed along several other propagation paths that crossed the L’Aquila seismogenic zone. Spectral analysis of the LF signals filtered in the frequency range 0.28 mHz to 15 mHz shows differences in the spectra for seismo-disturbed days when compared to those for either quiet or geomagnetically disturbed days. These spectral anomalies, which are only observed in the propagation path between NRK and Bari, contain signals with periods of about 10 min to 20 min. These periodic signals are absent both in the spectra of the undisturbed signals for the control paths, and in the spectra of the signals received during geomagnetic storms. The same changes in the spectral composition were observed in the analysis of LF (40 kHz) signals from the JJY transmitter in Japan that were received in Petropavlovsk-Kamchatsky (Russia) during the occurrence of three strong earthquakes with M ≥7.0. The results of this study support the theoretical prediction that the possible mechanism for energy penetration from the origin of an earthquake through the atmosphere and into the ionosphere is based on the excitation and upward propagation of internal gravity waves.